2021
DOI: 10.1186/s12951-021-01072-3
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine derived carbon dots: synthesis and applications in therapeutics, bioimaging and sensing

Abstract: Since the number of raw material selections for the synthesis of carbon dots (CDs) has grown extensively, herbal medicine as a precursor receives an increasing amount of attention. Compared with other biomass precursors, CDs derived from herbal medicine (HM-CDs) have become the most recent incomer in the family of CDs. In recent ten years, a great many studies have revealed that HM-CDs tend to be good at theranostics without drug loading. However, the relevant development and research results are not systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 165 publications
1
41
0
1
Order By: Relevance
“…Several current plant-derived CDs were prepared with the pyrolysis method (Additional file 1 : Table S1), and showed remarkable bioactivities for treating diseases. In comparison with the common hydrothermal method, this method still has higher temperatures but shorter time, which can meet the requirements of large-scale production [ 50 ], while the obtained CDs exhibit uniform particles distribution and smaller particle size [ 19 ], with certain fluorescence and lower QY(≤ 10%). Furthermore, our team previously illuminated the treatment of CDs synthesized using the high-temperature method in hemostatic and ulcerative diseases, with no significant undesirable affect in cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several current plant-derived CDs were prepared with the pyrolysis method (Additional file 1 : Table S1), and showed remarkable bioactivities for treating diseases. In comparison with the common hydrothermal method, this method still has higher temperatures but shorter time, which can meet the requirements of large-scale production [ 50 ], while the obtained CDs exhibit uniform particles distribution and smaller particle size [ 19 ], with certain fluorescence and lower QY(≤ 10%). Furthermore, our team previously illuminated the treatment of CDs synthesized using the high-temperature method in hemostatic and ulcerative diseases, with no significant undesirable affect in cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the chemically synthesized CDs with the complex manipulation and chemical reagent contaminating properties have a certain obstruction in the clinical translation. In contrast, the biomass-based CDs have naturally aroused wide attention because of cheap carbon source, low biotoxicity, simple synthesis process, and potential application [ 19 21 ]. Moreover, the obtained CDs have a portion of the functional groups from precursors compounds preserving on their surface, thus exerting a potential effect for treating the damage [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the material basis of its efficacy is not clear at present. Some scholars have found that the compounds contained in herbal medicines in the process of high-temperature processing can be transformed into CDs through dehydration, calcinations and carbonization, which have different biological activities from the original medicinal materials [ 38 , 39 , 40 ]. Therefore, in this study, we successfully obtained PGC-CDs from PGC and discovered PGC-CDs were approximately spherical, with an average particle size of 2.3 nm, and mainly contained C, O and N elements, as well as carboxyl, hydroxyl, amino and other functional groups, indicating that PGC-CDs have better water solubility, more uniform particle size and new pharmacological activity different from the original medicinal compound.…”
Section: Discussionmentioning
confidence: 99%
“…Although the synthesis of CDs from renewable bio-sources has its own challenges, it has been a desirable approach ( De and Karak, 2013 ), because of several advantages, like sustainability, low cost, added value to waste, pollution-free materials, and green preparation methods ( Liu et al., 2019c ; Liu et al., 2019b ; Singh et al., 2019 ; Yu et al., 2019 ; Ahmadi et al., 2020 ; Boruah et al., 2020 ; Wang et al., 2020a ; Liu et al., 2020a ; Lu et al., 2020 ; Das et al., 2021 ; Ding et al., 2021 ; Lou et al., 2021 ). Moreover, biomass-derived nanomaterials exhibit excellent water solubility, nontoxicity, and good biocompatibility ( Wang et al., 2020b ; Luo et al., 2021 ; Krishnaiah et al., 2022 ).…”
Section: Biomassmentioning
confidence: 99%